2022
DOI: 10.1186/s12876-022-02257-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of EMT-immune-related prognostic biomarkers CDKN2A, CMTM8 and ILK in colon cancer

Abstract: Colon cancer (CC) is a disease with high incidence and mortality rate. The interaction between epithelial-mesenchymal transition (EMT) and immune status has important clinical significance. We aim to identify EMT-immune-related prognostic biomarkers in colon cancer. The GEO2R and GEPIA 2.0 were utilized to calculate the differential expression genes between CC and normal mucosa. Immport, InnateDB and EMTome databases were used to define EMT-immune-related genes. We conducted batch prognostic analysis by TCGA d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 81 publications
1
14
0
Order By: Relevance
“…It is possible that this is the reason why people with high EMT scores have a poorer prognosis. EMT may interact with immunosuppres-sion either directly or indirectly, as shown by the results of a prior study [33]. Since immune cells are important biomarkers for immunotherapy, the influence of EMT on immunity is important and needs more studies.…”
Section: Discussionmentioning
confidence: 95%
“…It is possible that this is the reason why people with high EMT scores have a poorer prognosis. EMT may interact with immunosuppres-sion either directly or indirectly, as shown by the results of a prior study [33]. Since immune cells are important biomarkers for immunotherapy, the influence of EMT on immunity is important and needs more studies.…”
Section: Discussionmentioning
confidence: 95%
“…CDKN2A can be regarded as a promising biomarker of colon cancer ( 26 ). CDKN2A , as an important marker of epithelial-mesenchymal transition, tends to be upregulated in colon cancer ( 27 ). Cluster B had more mortality and advanced stage (stage III–IV) compared with cluster A.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, although the oncogenic effects of mutations and loss of CDKN2A are well established [53], unexpectedly high CDKN2A expression indicates a poor prognosis in a variety of tumors. Similarly, previous studies have shown that high CDKN2A expression is associated with poor prognosis in LIHC, COAD, and BLCA [54–57]. However, the mechanism by which CDKN2A acts as a tumor suppressor but leads to poor prognosis has not been clarified.…”
Section: Discussionmentioning
confidence: 97%